SEASONAL VARIATION OF PHYSICO-CHEMICAL FEATURES OF WATER SAMPLED FROM TIGA RESERVOIR, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
This study assessed the physico-chemical features and dissolved mineral elements of the water sampled from Tiga reservoir, Nigeria. The sampling period was between the months of May, 2014 to April, 2015, water samples were collected from a strategic point of effluent in cleaned bottles of average volume 250 ml. The physico-chemical and mineral elements were analysed in accordance to standard method using spectrophotometer. The results of the wet and dry seasons showed significant differences (p
Keywords: Climate, lake, ecology, component, health